Acute and Short-Term Outcomes of Percutaneous Transcatheter Mitral Valve Replacement in Children. (April 2021) - Maschietto, Nicola; Prakash, Ashwin; del Nido, Pedro; Porras, Diego
Abstract : Background: Despite the improvement of surgical techniques for mitral valve (MV) repair in children, mitral valve replacement (MVR) is sometimes still necessary. MVR and redo-MVR continue to be burdened by early postoperative mortality and long-term morbidity with only about 75% of these patients being alive or transplant-free 10 years after the initial MVR. Although transcatheter MVR (TMVR) is a well-established intervention in high surgical risk adults, only a few pediatric valve-in-valve case reports have been published. The purpose of this study was to describe our initial experience with the off-label use of the Sapien S3 valve for TMVR in a highly selected pediatric patient population. Methods: We conducted a retrospective analysis of pediatric patients who underwent TMVR at Boston Children's Hospital between October 2018 and July 2020. Results: Eight consecutive high surgical risk pediatric patients (median age, 9 years; range, 8–15) underwent TMVR (7 as valve-in-valve, 1 in a native MV). Each patient previously underwent multiple MV surgeries or MVR (median 4, range 2–5) and was highly symptomatic (Ross functional class 3 or 4). The indication for TMVR was mitral stenosis in 4 patients, regurgitation in 1, and mixed disease in 3. TMVR was successful in each patient, effectively reduced the left atrium and pulmonary hypertension ( P =0.012 and 0.043 respectively), and was carried out without significant complications. Conclusions: TMVR is an attractive alternative to MVR in high surgical risk patients. In this small series, TMVR was acutely effective and safe, with very encouraging early results. Abstract : Supplemental Digital Content is available in the text.